The Sienese school of painting in 1260-1300. On the problem of studying the images of Our Lady - Kovalenko, Natalya A. (Actual Problems of Theory and History of Art, 2012)
The article is devoted to the Early Sienese school of painting and especially to the works of those artists who were closely connected with the Byzantine tradition. Most of these works are the icons of the Virgin. The special veneration of the Mother of God in Siena called to life some new variants of the iconography in the works of Sienese artists (Guido da Siena, Guido di Graziano, Dietisalvi di Speme) and some others (Coppo di Marcovaldo). Some iconographic themes resulted out of special ceremonies and feasts in honor of the Virgin.
Keywords: Sienese school of painting; Italian art; Proto-Renaissance; Early Renaissance in Italy; Trecento; images of Madonna; Maestà; Dietisalvi di Speme; Guido da Siena; Duccio di Buoninsegna; altarpiece Sienese school of painting; altarpiece